Desain Organisasi Sekolah Yang Adaptif: Menjawab Tantangan Pendidikan Di Era Digital - Ahmad Rizky Ardi Pratama; Hafizah Ismayati; Nurul Fadhilah; Ahmad Mukhlasin (Lembaga Pengembangan Kinerja Dosen, 2024)
Rapid digital transformation has created significant opportunities and challenges for education systems around the world. This article explores the concept of adaptive school organizational design in response to these changes, focusing on how educational institutions can leverage technology to improve the quality and efficiency of learning. The study explores key elements of adaptive organizational design, including flexible organizational structures, a culture of innovation, and visionary leadership. Opportunities identified include increasing accessibility of education through e-learning, greater personalization of learning, and collaboration enhanced by digital technologies. However, significant challenges also arise, such as the need for high digital literacy, resistance to change, and gaps in technological infrastructure. By analyzing the needs and challenges faced by schools in the digital era, this article develops a model of school organizational design that can be applied to improve educational effectiveness. Practical recommendations for stakeholders are also provided to help implement organizational change in schools. This study is expected to make significant contributions to the academic literature and educational practice, as well as provide guidance for policymakers and education practitioners in developing effective adaptation strategies in the digital era.